Nasal Powder Formulations: In-Vitro Characterisation of the Impact of Powders on Nasal Residence Time and Sensory Effects - Trenkel, Marie (Pharmaceutics, 2021)
Nasal drug delivery is still primarily associated with locally-effective drugs, but next-generation products utilising the benefits of nasal administration—such as easy access to a relatively permeable mucosa, the presence of immunocompetent cells, and a direct route to the brain—are under investigation. Nasal powders offer the potential to improve the drugs’ effects by providing higher resistance against the mucociliary clearance, and thus prolonging the contact time of the drug with its target site. However, suitable and easy-to-use in-vitro setups tailored to the characterisation of this effect are missing. In this study, a selection of excipients for powder formulations were used to evaluate the applicability of different methods which investigate the influence on the contact time. The combination of the assessment of rheological properties, dynamic vapour sorption, and adhesiveness on agar–mucin plates was found to be a valuable predictive tool. For the additional assessment of the sensations associated with the close contact of powders and the mucosa, a slug mucosal irritation assay was conducted and adapted to powders. These methods are regarded as being especially useful for comparative screenings in early formulation development.